If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8x = 2(6x + -12) Combine like terms: 4x + 8x = 12x 12x = 2(6x + -12) Reorder the terms: 12x = 2(-12 + 6x) 12x = (-12 * 2 + 6x * 2) 12x = (-24 + 12x) Add '-12x' to each side of the equation. 12x + -12x = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 0 = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 0 = -24 + 0 0 = -24 Solving 0 = -24 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 | | -47.62=k+89.2 | | 2x^2+22x+54=0 | | (7+3y)2= | | 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x | | x^3+2x^2+x= | | (x-1)(-6x+6)= | | 7x-5(x+1)+9=19 | | -16.49(4)+5.2= | | ln(5x-13)=4 | | y(2y-8)=0 |